Difference in Perception of Pregnancy Risk in Two Maternal Age Groups - Taghizadeh, Ziba (J Clin Diagn Res, 2017)
INTRODUCTION: Various health risks and complications may happen during pregnancy for both the mother and her child. Women should be informed of the risk associated with their pregnancy. AIM: To compare the differences of perception of pregnancy risk of two maternal age groups of healthy nulliparous women. MATERIALS AND METHODS: In an analytical, descriptive cross-sectional study, 240 nulliparous pregnant women (160 women aged 18 to 35 years as a normal age group and 80 women < 18 years as a high risk age group) were randomly selected. Women were asked to complete questionnaire which included sociodemographic characteristics, pregnancy history, perception of pregnancy risk and pregnancy related anxiety. RESULTS: Overall, women of < 18 years (high-risk group) perceived the risks of pregnancy higher than those of 18-35 years age women (reference group). Women in high-risk group rated their risks for herself, having haemorrhaging, having a cesarean birth and dying during pregnancy to be significantly higher than reference group. There was a statistically significant relationship between maternal age and perception of pregnancy risk (p<0.003). There was also a statistically significant relationship between pregnancy related anxiety and perception of pregnancy risk (p<0.002). CONCLUSION: Women’s perception of pregnancy risk is different in various maternal age groups. Maternal age can be considered as one of the important factors affecting perception of pregnancy risk. By routine screening of perception of pregnancy risk during prenatal care more effective risk consulting model could be designed.